Free time and its use depending on the professional status of respondents – selected results of the research on the students’ free time - Miłaszewicz, Danuta (Czas wolny i jego wykorzystanie a status zawodowy respondentów – wybrane wyniki dwukrotnych badań zasobu czasu wolnego studentów, 2020)
The aim of this study is to analyze the daily free time budget of students, their free time structure and to show the possible differences in free time management depending on the respondents’ professional status. The primary method of collecting research material was a diagnostic survey, including the questionnaire developed by the author. The research was conducted twice, in 2018 and 2020, each time at two academic centres in Poland. The research results show that students are a very diverse social group in terms of activities undertaken in their free time, and the visible differences in how it is spent are linked to the income source of the respondents
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2020; vol. 64, nr 8, s. 104-117